Physiological, biochemical and productive changes in sesame genotypes subjected to different rates of water replenishment - Maria S. R. Lima; Maria do S. Rocha; Alberto S. de Melo; Wellison F. Dutra (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT The sesame crop has stood out due to the high nutritional content of its seeds, in addition to being able to be cultivated in the tropical and subtropical regions such as Northeast Brazil. Thus, it is necessary to identify the physiological, biochemical and productive changes related to the tolerance to stress. Objective of this study was to evaluate the physiological, biochemical and productive aspects of sesame genotypes as a function of different rates of water replenishment. The experiment was carried out at the Embrapa Cotton Experimental Unit, located in the municipality of Barbalha-CE, Brazil, under field conditions. The experiment was carried out in a randomized complete block design, with treatments in a factorial scheme (4 × 6), corresponding to four irrigation depths (40, 70, 100 and 130% ETo) and six sesame genotypes (G1 = T3-EGSGO3; G2 = T7-EGSGO7; G3 = T5-EGSGO5; G4 = T2-EGSGO2; G5 = T6-EGSGO6; G6 = T4-EGSG04), with three replicates. Data corresponding to the following variables were collected: leaf area, photosynthetic pigments, relative water content in leaf, electrolyte leakage, catalase, peroxidase, yield and oil content. The genotypes did not differ statistically and there were differences in the variables between the water replacement rates. Increments in growth and, consequently, in production, enzymatic activity, oil content and maximum production potential were observed with water depths between 75 and 90% ETo. Contents of chlorophyll a and b, total chlorophyll and carotenoids, were increased with the application of 80% ETo.